Social Health Insurance in Malaysia – Lessons from Thailand and South Korea - Nathaniel Lee (Kajian Malaysia, 2012)
The rising cost of healthcare in Malaysia has had a detrimental effect on access to care. In 2009, the major sources of financing for national healthcare expenditures were via government subsidies and out-of-pocket expenditures. Although social security schemes are in place to ease government spending, these schemes have not been inclusive enough to significantly alter expenditure trends. The suggestion for a national social health insurance (SHI) scheme was put forth in the 1996 Seventh Malaysia Plan. SHI schemes have formed the basis for successful health system financing initiatives in various countries. South Korea and Thailand are two Asian countries that have undergone progressive economic development and successful transitions to SHI-based schemes. Drawing from the experiences of these two countries, certain recommendations can be made to create a positive environment for a transition to a SHI-based healthcare system in Malaysia. These intertwined criteria include enabling appropriate institutional capacities, directly addressing the rising cost of healthcare, and ensuring the continuity of universal coverage of care.